Bee-Sensor-C: An Energy-Efficient and Scalable Multipath Routing Protocol for Wireless Sensor Networks - Xuelian Cai; Yulong Duan; Ying He; Jin Yang; Changle Li (International Journal of Distributed Sensor Networks)
A wireless sensor network (WSN) is composed of a large collection of sensor nodes with limited resources in terms of battery supplied energy, processing capability, and storage. Therefore, the design of an energy-efficient and scalable routing protocol is a crucial concern for WSN applications. In this paper, we propose Bee-Sensor-C, an energy-aware and scalable multipath routing protocol based on dynamic cluster and foraging behavior of a bee swarm. Bee-Sensor-C is an evolution from BeeSensor which is a bee-inspired routing protocol for WSNs. First of all, through introducing a dynamic clustering scheme, Bee-Sensor-C offers parallel data transmissions close to the event area. This evolution reduces routing overhead and improves the scalability. Moreover, Bee-Sensor-C adopts an enhanced multipath construction method in order to achieve the balance of the network energy consumption. Besides, Bee-Sensor-C can well support the multicluster scenario. Through simulations, the network performance is evaluated and the results demonstrate that Bee-Sensor-C outperforms the existing protocols in terms of energy efficiency, energy consumption balance, packet delivery rate, and scalability.